Crosstalk between dysregulated amino acid sensing and glucose and lipid metabolism in colorectal cancer - Wang, Danning; Zou, Shaomin; Ding, Junkang; Gao, Chang; Wang, Jianwei; Tang, Zhe (Frontiers in Oncology, 2025)
Cancer cells reprogram the metabolism of glucose, lipids, and proteins (amino acids) to meet their energy needs during tumor initiation and progression. Amino acid sensing pathways play rucial roles in the progression and spread of colorectal cancer (CRC), but the crosstalk between these pathways and glucose and lipid metabolism has not been systematically elucidated. We summarize the roles of key amino acids in CRC, the corresponding nutrient sensors, the associated dysregulated signaling pathways, and their subcellular localization. Furthermore, we highlight how disrupted amino acid sensing forms an integrated regulatory network that modulates glucose and lipid metabolism through multiple signaling cascades. These insights reveal both opportunities for clinical translation and unresolved challenges in the field. We believe that this comprehensive review will stimulate further research in this emerging area and draw significant attention from both the scientific community and broader audiences. This review aims to identify new diagnostic markers, therapeutic targets, and prognostic indicators by enhancing the understanding of nutrient metabolic pathway interactions.